The Results of Using Guidance Activities to Develop the Growth Mindset in Managing Emotions and Stress of Grade 11 Students - Buakong, Sirilak; Onjaiuea, Paveena; Kaewchinda, Marid (Academic MCU Buriram Journal, 2023)
The purpose of this research were: 1) to create guiding activity for developing the growth mindset in managing emotions and stress of Grade 11 students and 2) to study the growth mindset in managing emotions and stress of Grade 11 students. The methodology research was the quasi-experimental. The population was 455 students from grade 11 who were studying in semester 2 of the academic year 2021. The sample groups were one classroom by random sampling method (40 students). The research instruments consisted of 1) the guidance activities to develop the growth mindset in managing emotions and stress, 2) the measurement of the growth mindset in managing emotions and stress form, 3) the students’ records of learning the guidance activities to develop the growth mindset in managing emotions and stress, and 4) the satisfaction questionnaire of the researcher and the guidance activities to develop the growth mindset in managing emotions and stress. The data were analyzed by using mean, standard deviation, parametric tests, and paired-sample t-test. The research result found that: 1. The simple group had higher level of the growth mindset in managing emotions and stress than before using the experiment with the significance level at the .05 level 2. Most students had high satisfaction level after joining the guidance activities.